Dire emotions and lethal behaviors: eclipse of the life instinct - Stewart, Charles T. (Routledge, 2008)
How the innate affects work -- Optimal vs. violent expression of affect: a new way to understand the -- Emergence of each of these outcomes -- Death and rebirth of the life instinct -- Vivienne Loomis: suicide -- Kipland Kinkel: killing of parents and others -- Eric Harris and Dylan Klebold: multiple homicides followed by suicides -- Sinedu Tadesse: homicide followed by suicide -- Gloria: panic leading to homicide, Peter: fury leading to killing of mother and sisters -- Little father time: homicides followed by suicide -- Lethal conditions and psychological treatment -- Epilogue